Optimization of the Antenna Array with Cosequences Pattern - A. D. Frantsuzov (Известия высших учебных заведений России: Радиоэлектроника)
The method of partial directional diagrams (PDD) synthesized vertical omnidirectional in azimuth plane antenna arrays (AR) with cosequences PDD form in the vertical plane. The AR optimum height on the criterion of maximum gain is determinated. It is shown that the optimum height of AR de-pends significantly on the losses in the microwave cables and in the signal divider.